Phylogenetic diversity metrics from molecular phylogenies: modelling expected degree of error under realistic rate variation. Issue 1 (23rd October 2020) - Ritchie, Andrew M.; Hua, Xia; Cardillo, Marcel; Yaxley, Keaghan J.; Dinnage, Russell; Bromham, Lindell
Abstract: Aim: Phylogenetic diversity or phylo‐diversity measures use information about evolutionary history and relationships to inform conservation priorities. These metrics are usually derived from the branches of molecular phylogenies. But inferring phylogenetic timescale from molecular data relies on many assumptions about the evolutionary process, most of which are based on statistical convenience rather than biological information. Here we ask whether known patterns of variation in rate of molecular evolution can lead to errors in phylo‐diversity measures. Location: Global. Methods: We generated sequences with biologically realistic rate variation, parameterized by empirically well‐supported relationships between species traits, macroevolutionary patterns and rate of molecular evolution. We then tested how well commonly used phylo‐diversity measures from these phylogenies reflected the true evolutionary history. Results: We show that reconstructed Faith's phylogenetic diversity (FPD) measures differ from true values by an average of about 10% and up to 38%. Species rankings based on evolutionary distinctness (ED) are also affected by rate variation, with the ranks of taxa changing by up to 10‐11 positions after estimation. Main conclusions: We have shown that realistic levels of rate variation can generate error in FPD and ED measures that could potentially influence prioritization ranking. Studies using metrics based on molecular phylogenetic branch lengths should consider the likely effect of uncertainty in phylogenetic reconstruction on their conclusions.